Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum Dan Sesudah Akuisisi (Studi Kasus Pada Perusahaan Go Public Non Bank Yang Terdaftar Di BEI Tahun 2012) - Jean Natawigena; Fitra Oliyan (Jurusan Akuntansi Politeknik Negeri Padang, 2017)
This final project aims to analyze the comparison of financial performance of non-bank go public companies listed on the IDX in 2012 before and after the acquisition. This research is quantitative research. The study was conducted using financial ratios, namely: ROE (Return On Equity), DER (Debt to Equity Ratio), EPS (Earning Per Share), TATO (Total Asset Turn Over), CR (Current Ratio), EVA (Economic Value Added), and MVA (Market Value Added). Measurement of financial performance in each company uses secondary data. The population in this study were all companies listed on the IDX that had made acquisitions, and the company announced its acquisition activity in 2012. The method in taking this study using purposive sampling, so that there were eight companies included in the criteria of this study, then the period of observation is 2011-2014. The test tool used is the SPSS version 20. The results of the study using one sample paired t test showed that the companies that acquired did not have differences in ROE, DER, EPS, TATO, CR, EVA and MVA before and after the acquisition.